Substrate Specificity of Acyltransferase Domains for Efficient Transfer of Acyl Groups - Shen, Jie-Jie; Chen, Fu; Wang, Xiao-Xuan; Liu, Xiao-Fang; Chen, Xin-Ai; Mao, Xu-Ming; Li, Yong-Quan (Frontiers in Microbiology, 2018)
Acyltransferase domains (ATs) of polyketide synthases (PKSs) are critical for loading of acyl groups on acyl carrier protein domains (ACPs) via self- and trans-acylation reactions, to produce structurally diverse polyketides. However, the interaction specificity between ATs and unusual acyl units is rarely documented. In Streptomyces tsukubaensis YN06, we found that AT4FkbB (an AT in the fourth module of tacrolimus (FK506) PKS) transferred both allylmalonyl (allmal) and emthylmalonyl (ethmal) units to ACPs, which was supposed responsible for the production of both FK506 and its analogue FK520, respectively. Mutations of five residues in AT4FkbB (Q119A, L185I-V186D-V187T and F203L) caused decreased efficiency of allmal transfer, but a higher ratio of ethmal transfer, supposedly due to less nucleophilic attacks between Ser599 in the active site of AT4FkbB and the carbonyl carbon in the allmal unit, as observed from molecular dynamics simulations. Furthermore, reverse mutations of these five residues in ethmal-specific ATs to the corresponding residues of AT4FkbB increased its binding affinity to allmal-CoA. Among these residues, Val187 of AT4FkbB mainly contributed to allmal recognition, and V187K mutant produced less FK520 than wild type. Our findings thus suggested that five critical residues within AT4FkbB were important for AT functionality in polyketide extension and potentially for targeting biosynthesis by generating desirable products and eliminating undesirable analogues.